Analysis of threshold voltage instabilities in semi-vertical GaN-on-Si FETs. (30th January 2020) - Mukherjee, Kalparupa; Borga, Matteo; Ruzzarin, Maria; De Santi, Carlo; Stoffels, Steve; You, Shuzhen; Geens, Karen; Liang, Hu; Decoutere, Stefaan; Meneghesso, Gaudenzio; Zanoni, Enrico; Meneghini, Matteo
Abstract: We present a first study of threshold voltage instabilities of semi-vertical GaN-on-Si trench-MOSFETs, based on double pulsed, threshold voltage transient, and UV-assisted C – V analysis. Under positive gate stress, small negative V th shifts (low stress) and a positive V th shifts (high stress) are observed, ascribed to trapping within the insulator and at the metal/insulator interface. Trapping effects are eliminated through exposure to UV light; wavelength-dependent analysis extracts the threshold de-trapping energy ≈2.95 eV. UV-assisted CV measurements describe the distribution of states at the GaN/Al2 O3 interface. The described methodology provides an understanding and assessment of trapping mechanisms in vertical GaN transistors.